2015
DOI: 10.1103/physrevb.91.155312
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of a two-dimensional electron gas dressed by light

Abstract: We show theoretically that the strong interaction of a two-dimensional electron gas (2DEG) with a dressing electromagnetic field drastically changes its transport properties. Particularly, the dressing field leads to the giant increase of conductivity (which can reach thousands of percents), results in nontrivial oscillating dependence of conductivity on the field intensity, and suppresses the weak localization of 2DEG. As a consequence, the developed theory opens an unexplored way to control transport propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 44 publications
2
63
1
Order By: Relevance
“…However, in general it is to be expected that an oscillating vector potential would lead to coherent excited pairs with an oscillating center of mass motion, with a more substantial modification of the density of states. The change of the energy spectrum of electrons, dressed by an electromagnetic field, is, in principle, analogous to the dynamic Stark effect in atom physics [16] (and similarly for a two-dimensional electron gas [17]). Such dressed states have recently been put forward in the analysis of the microwave response of superconducting atomic point contacts [18,19].…”
mentioning
confidence: 99%
“…However, in general it is to be expected that an oscillating vector potential would lead to coherent excited pairs with an oscillating center of mass motion, with a more substantial modification of the density of states. The change of the energy spectrum of electrons, dressed by an electromagnetic field, is, in principle, analogous to the dynamic Stark effect in atom physics [16] (and similarly for a two-dimensional electron gas [17]). Such dressed states have recently been put forward in the analysis of the microwave response of superconducting atomic point contacts [18,19].…”
mentioning
confidence: 99%
“…It follows from the scattering probability (12) that the dependence arises from the Bessel function which decreases with increasing the intensity, I. Therefore, the scattering time in 2DEG, τ , increases with increasing intensity of the dressing field 15,16 . If the initial scattering time in unirradiated 2DEG, τ 0 , is large enough (the dashed line in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such a bound electron-field system, which was called "electron dressed by field" (dressed electron), became a commonly used model in modern physics 13,14 . Recently, we demonstrated that strong interaction between 2DEG and a high-frequency electromagnetic field drastically suppresses the scattering of dressed electrons 15,16 . Since the spin relaxation depends on both the mechanism of spin-orbit interaction and scattering processes, one can expect that the spin relaxation time is strongly affected to the dressing electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…These electrons with substantially modified energy dispersions, referred to as "dressed states"', became a commonly used model in present-day lowdimensional physics. [36][37][38][39][40][41] One of the first significant achievements has been the demonstration of a metal-insulator transition in graphene 42 , which drastically affected the electron tunneling and the Klein paradox. 43,44 Important collective properties such as exchange and correlation energies are also affected by the presence of an energy gap, 45 and spin dynamics on the surface of a three-dimensional topological insulator 46 is also modified.…”
Section: Introductionmentioning
confidence: 99%